Misuse and addiction to mobile phone in a sample of first-grade secondary school students of Palermo. (30th September 2020) - Pizzo, S; Costantino, C; Giliberti, D; Calò, I; Vella, C; Conforto, A; Sannasardo, C; Gambino, R; Casuccio, A
Abstract: Background: Nowadays, smartphone overuse affects massively teenagers and young adults. From 2014 to 2018 in Italy, for the 11-17 years age group, there has been an increase from 79.9% to 85.8% of daily mobile phone users. This project aims to investigate usage prevalence and misuse/addiction of mobile phones in a representative sample of first-grade secondary school students of the Province of Palermo, Italy, carrying out educational interventions to promote a proper and conscious use of smartphone. Materials and Methods: An anonymous, standardized and previously validated pre-intervention questionnaire consisting of 39 items on general socio-demographic characteristics, attitudes and habits regarding smartphone usage, was administered online to 10-15 years old students of the Palermo's Province. Moreover, two additional sets of 11 and 15 items contributed to calculate a Misuse and an Addiction Score, respectively. After administration, educational interventions aimed at promoting the correct and conscious use of the smartphone, were carried out. Results: A total of 1600 students belonging to 16 schools, responded to the questionnaire. 93% of the sample had a personal smartphone and 84% had a personal profile on at least one social network. About 15% of the sample experienced cyber bullying episodes and 30% accessed to adult content online (38% of parents didn't set parental control on the devices). Overall, 78.3% of the sample showed a moderate to severe misuse and 38.3% a moderate to severe addiction to mobile phones. Conclusions: The uncontrolled and unconscious use of smartphones among adolescents exposes to different health risks including psycho-social and cognitive-relational problems. Results obtained demonstrate high levels of misuse and addiction to mobile devices in a representative sample of students in a developed Country, suggesting the need to implement educational interventions and the development of guidelines to encourage a responsible use of smartphones. Key messages: The present study highlights an uncontrolled and unconscious use of mobile phones among 11-15 years old aged students in Southern Italy. The implementation of educational intervention at school and the development of guidelines regulating smartphone usage among adolescents, should represent a future global health priority.